INFORMATIVE COMPTENCE AS A COMPONENT OF TEACH (Journal of Information Technologies in Education (ITE), 2010)
Possibilities of forming of informatics’ competence are considered as a professional competence component of future physics teacher in Universities
Keywords: educational process; Informatichna competence; planning of pedagogical environments; teacher of physics